2019
DOI: 10.20517/2394-4722.2019.003
|View full text |Cite
|
Sign up to set email alerts
|

Muscle mitochondria and oxidative metabolism as targets against cancer cachexia

Abstract: Cancer cachexia is a debilitating syndrome mainly characterized by muscle and fat wasting, leading to the progressive loss of body weight and complicating the management of cancer patient. In particular, the loss of muscle weight is a negative prognostic factor, being associated with chemotherapy toxicity and reduced survival. Increased inflammation and protein dysmetabolism are some of the impairments that lead to muscle wasting in cancer patients. Together with these alterations, tumor growth and chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Beyond the regulation of the mitochondrial biogenesis, PGC-1a induces the activation of the antioxidant defenses (60). Consistently, the ablation of PGC-1a blunts some of the effects induced by exercise training in the skeletal muscle (11), and reduces the levels of different antioxidant enzymes (54). The other way round, PGC-1a overexpression in the tibialis anterior muscle decreases oxidative stress while increasing the antioxidant defenses in a model of immobilization-induced muscle atrophy (62).…”
Section: Exercise Counteracts Cachexia Modulating the Redox Homeostasismentioning
confidence: 77%
See 1 more Smart Citation
“…Beyond the regulation of the mitochondrial biogenesis, PGC-1a induces the activation of the antioxidant defenses (60). Consistently, the ablation of PGC-1a blunts some of the effects induced by exercise training in the skeletal muscle (11), and reduces the levels of different antioxidant enzymes (54). The other way round, PGC-1a overexpression in the tibialis anterior muscle decreases oxidative stress while increasing the antioxidant defenses in a model of immobilization-induced muscle atrophy (62).…”
Section: Exercise Counteracts Cachexia Modulating the Redox Homeostasismentioning
confidence: 77%
“…6). Using such an approach, different classes of drugs have been proven effective in reverting cancer-induced muscle wasting by mimicking some of the beneficial effects induced by exercise (11). Notably, trimetazidine (TMZ) increases muscle cross-sectional area and strength in C26-bearing mice, coupled with increased oxidative metabolism and mitochondrial mass (78).…”
Section: Potential Impact Of Antioxidants and Exercise Mimetics In Camentioning
confidence: 99%
“…The improvement of mitochondrial function is the main mechanism underlying the effectiveness of endurance exercise in counteracting the loss of muscle mass and function in cancer cachexia, and the above-mentioned mitochondria-targeting approaches can be considered as exercise mimetics [ 32 ]. Considering that exercise feasibility in oncology patients is limited, because of several issues related to the cancer itself or to other comorbidities, rendering the patient not eligible or even exercise intolerant [ 33 ], SS-31, mimicking some of the beneficial effects of exercise, could widen the target audience for exercise-based interventions by both promoting exercise tolerance and improving the effectiveness of physical activity, as previously reported in sarcopenic aged mice [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, an increase in muscle mass was reported in Pin et al [ 236 ], whilst cancer cachexia was not counteracted in Wang et al [ 237 ] in PGC-1α overexpressing muscles LLC-bearing mice. Both studies reported an increase in tumor mass [ 236 , 237 ], highlighting the cross-talk between muscle and tumor and revealing a possible limitation of increasing the expression of PGC-1α in muscle in cancer cachexia [ 238 ]. In addition to improving mitochondrial oxidative capacity, exercise modulates muscle metabolism by enhancing GLUT-4 translocation at the sarcolemma [ 239 ], thereby increasing the productivity of the glycolytic pathway and counteracting insulin resistance [ 239 , 240 , 241 ].…”
Section: Skeletal Muscle Metabolism In Cancer Cachexiamentioning
confidence: 99%